2000
DOI: 10.1136/fn.82.2.f167
|View full text |Cite
|
Sign up to set email alerts
|

Proximity to maternity services and stillbirth risk

Abstract: A study of all 77 995 live births and 1234 stillbirths to mothers living in West Cumbria from 1950 to 1989 found no significant increase in stillbirth risk with distance of mother's residence from the first or second nearest maternity services, after allowing for year of birth, father's social class, and birth order. (Arch Dis Child Fetal Neonatal Ed 2000;82:F167-F168)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 4 publications
0
24
2
1
Order By: Relevance
“…There was no evidence of increasing risk of stillbirth with increasing travel time to hospital (results not presented), confirming the results in Parker and colleagues. 3 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no evidence of increasing risk of stillbirth with increasing travel time to hospital (results not presented), confirming the results in Parker and colleagues. 3 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, we investigated stillbirth risk in Cumbria in relation to hospital accessibility using a larger dataset than that considered by Parker and colleagues. 3 …”
mentioning
confidence: 99%
“…Access to maternity care is often limited in rural areas and travel time is longer. Very few studies have been performed on this issue 7,8 . None of them found a significant influence of travel time on perinatal mortality.…”
Section: Introductionmentioning
confidence: 98%
“…When access to emergency obstetric services is examined from the perspective of distance to a hospital, there is more convincing evidence about the relationship between the distance from maternal residence to hospital obstetric services and clinical outcomes. Although early studies found no association between adverse outcomes and the distance from maternal residence to a hospital, further research has demonstrated that perinatal mortality and other adverse neonatal outcomes increase with increasing distance from a hospital setting . A Canadian study of more than 150,000 births found that perinatal mortality was highest in communities more than 4 hours from maternity services, and preterm birth was more likely among individuals without access to local services .…”
Section: Introductionmentioning
confidence: 99%
“…The proximity to emergency obstetric services, measured as either distance or time, is a persistent and critical concern for those who plan and deliver maternal and newborn care. Previous literature has focused on either the time within an institution from identification of an emergency to the availability of emergency obstetric services, such as cesarean birth, or the distance from maternal residence to hospital maternity services . Within hospitals, optimizing the decision‐to‐delivery interval, that is, the time from which when the need for a cesarean is identified until birth, is seen as a means to ensuring safety and high‐quality care .…”
Section: Introductionmentioning
confidence: 99%